Revolutionizing Fast Food Marketing Strategy using Kotler's Approach: Merevolusi Strategi Pemasaran Makanan Cepat Saji menggunakan Pendekatan Kotler - Neni Dwi Riris Setyowati; Kumara Adji Kusuma (Academia Open, 2024)
This study investigates marketing strategies and service quality's impact on consumer decisions to purchase fast food at M2M, employing Kotler's marketing mix strategy. Using a qualitative approach, the research explores elements of the marketing mix—product, pricing, promotion, and distribution—influencing marketing success. Interviews with M2M managers and on-site observations provide insights. Findings highlight segmentation, targeting, and positioning processes, emphasizing mass marketing via social media. Key aspects include market penetration through affordable pricing and forward integration by collaborating with street food vendors. Implications suggest enhancing product innovation and understanding competitors' offerings. This research contributes to understanding effective marketing strategies in the fast-food industry, informing future business practices. Highlight: Impact of marketing mix on consumer behavior. Influence of service quality on purchase decisions. Application of Kotler's strategy in fast food industry. Keyword: Marketing strategy, Service quality, Consumer decisions, Fast food industry, Kotler's marketing mix.